Switching of primary health care providers among self-paid health insurance participants in Denpasar, Bali, Indonesia - Rai Riska Resty Wasita; Ni Made Sri Nopiyani; Pande Putu Januraga (Universitas Udayana, 2018)
Background and purpose: The number of National Health Insurance (NHI) participants switching their primary healthcare (PHC) providers is increasing and dominated by self-paid participants. This switching could result in unequal distribution of NHI participants and amount of capitation among PHC providers. This study aims to explore the reasons underlying self-paid NHI participants to switch PHC providers. Methods: This is a qualitative study using in-depth interviews with a total of 14 informants recruited purposively, consisted of ten NHI selfpaid participants who had switched and four participants who intend to switch PHC providers. Informants were recruited by approaching NHI participants at BPJS counters and inviting participants through social media. Semi-structured interview guide incorporated the aspects of Consumer Switching Behavior Model. The interviews explored four aspects of participants’ intention to switch providers including inconvenience, service encounter failures, core health service failures, and attraction by competitor. The verbatim transcripts were analyzed thematically. Results: Self-paid NHI participants in this study cited four main reasons for switching PHC providers. The first reason is inconvenience in accessing PHC provider’s services due to long distance, long waiting times, unsuitable opening hours, and poor facilities. Secondly, patients cited the poor interaction between healthcare providers and patients specifically, lack of attentiveness, poor eye contact, poor delivery of health information, lack of consideration of patients’ opinions, and lack of responsiveness to patients’ complaints. The third reason is core healthcare service failures, including hasty examinations, inaccurate diagnoses, and errors in prescribing medication. Finally, informants reported that they wished to switch PHC providers due to the attractiveness of other providers, in terms of facilities availability, professionalism of healthcare providers, additional health programs, and ease of access to referral healthcare facilities. Conclusion: Self-paid NHI participants’ intention to switch PHC providers was mainly attributed to the perceived poor healthcare quality of the provider and superiority of the others. Continuous quality improvement should be undertaken by PHC providers to increase participants’ loyalty.